Formation and control of the E2∗ center in implanted β-Ga2O3 by reverse-bias and zero-bias annealing. (20th August 2020) - Zimmermann, C; Førdestrøm Verhoeven, E; Kalmann Frodason, Y; Weiser, P M; Varley, J B; Vines, L
Abstract: Deep-level transient spectroscopy measurements are conducted on β -Ga 2 O 3 thin-films implanted with helium and hydrogen (H) to study the formation of the defect level E 2 ∗ ( E A = 0.71 eV) during heat treatments under an applied reverse-bias voltage (reverse-bias annealing). The formation of E 2 ∗ during reverse-bias annealing is a thermally-activated process exhibiting an activation energy of around 1.0 eV to 1.3 eV, and applying larger reverse-bias voltages during the heat treatment results in a larger concentration of E 2 ∗ . In contrast, heat treatments without an applied reverse-bias voltage (zero-bias annealing) can be used to decrease the E 2 ∗ concentration. The removal of E 2 ∗ is more pronounced if zero-bias anneals are performed in the presence of H. A scenario for the formation of E 2 ∗ is proposed, where the main effect of reverse-bias annealing is an effective change in the Fermi-level position within the space-charge region, and where E 2 ∗ is related to a defect complex involving intrinsic defects that exhibits several different configurations whose relative formation energies depend on the Fermi-level position. One of these configurations gives rise to E 2 ∗, and is more likely to form if the Fermi-level position is further away from the conduction band edge. The defect complex related to E 2 ∗ can become hydrogenated, and the corresponding hydrogenated complex is likely to form when the Fermi level is close to the conduction band edge. Di-vacancy defects formed by oxygen and gallium vacancies (V O −V G a ) fulfill several of these requirements, and are proposed as potential candidates for E 2 ∗ .